2014
DOI: 10.5993/ajhb.38.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Beliefs of Patients with Chronic Liver Disease

Abstract: Objectives To explore knowledge, attitudes, behaviors, and barriers to care among patients with chronic liver disease (CLD). Methods Three separate, one-time-only, 60-minutes focus group sessions were audio-recorded, transcribed, and analyzed using an editing style of analysis. Results In total, 13 focus group participants provided 254 discrete comments. Emerging themes included: negative lifestyles/behaviors, lack of CLD knowledge, negative attitudes/emotions, stigma and negativity, health insurance, inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 18 publications
(16 reference statements)
1
44
0
2
Order By: Relevance
“…The knowledge regarding LC definition was good among all the participants and this could be attributed to that LC and hepatic disorders have drawn the attention of the researchers and health authorities around the world (13) .The knowledge about the risk factors was good among most of the participants regarding the hepatitis virus and fatty liver disease. On the other hand most of the subjects underestimated the effects of obesity, infection, toxicity and autoimmune conditions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The knowledge regarding LC definition was good among all the participants and this could be attributed to that LC and hepatic disorders have drawn the attention of the researchers and health authorities around the world (13) .The knowledge about the risk factors was good among most of the participants regarding the hepatitis virus and fatty liver disease. On the other hand most of the subjects underestimated the effects of obesity, infection, toxicity and autoimmune conditions.…”
Section: Discussionmentioning
confidence: 94%
“…This could be due to that the younger and highly educated subjects have good access to new technology from which they could gain a lot of information regarding this disorder. However, many studies showed that older population are more vulnerable to LC thus they may have good knowledge than younger subjects (5,13) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients with liver disease worldwide have suggested that patients’ explanations of symptoms (such as fatigue and tiredness) may be influenced by folk health beliefs, which affect the health behaviours and management of the disease, including adopting new lifestyles or alternative/traditional treatments (Brener et al, ; Burnham et al, ; Owiti, Greenhalgh, Sweeney, Foster, & Bhui, ). Traditional treatments are often related to cultural beliefs, including spiritual healing (Fang & Stewart, ), remedial or healing herbs (Fang & Stewart, ; Giles‐Vernick et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is for this reason, therefore, that they avoid sharing with others the diagnosis, to protect themselves from the discrimination of the population. 23 On the other hand, there is also the prejudice regarding the hepatitis carriers, caused by the lack of knowledge of the population and fear of the transmissibility, which has also contributed to the removal of people connected with the sick person. "Fear of disease is a historical fact, just as the fear of becoming infected by something is an inherent condition of ignorance and the generation of stigmata, which compromises the social relations, family dynamics and the perception of oneself".…”
Section: Stigma Of Hepatic Diseasementioning
confidence: 99%